2012
DOI: 10.1007/978-3-642-30214-5_17
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Recognition of Affective Body Movement in a Video Game Scenario

Abstract: Abstract. This study aims at recognizing the affective states of players from non-acted, non-repeated body movements in the context of a video game scenario. A motion capture system was used to collect the movements of the participants while playing a Nintendo Wii tennis game. Then, a combination of body movement features along with a machine learning technique was used in order to automatically recognize emotional states from body movements. Our system was then tested for its ability to generalize to new part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Most systems take input data from motion capture equipment, such as the VICON system [17] or gaming devices like Nintendo Wii [20] because these devices could provide great details about body motion. The most noticeable work in gestural emotion detection has been done by Camurri and the Infomus Lab [21].…”
Section: B Emotion Detection From Body Languagementioning
confidence: 99%
“…Most systems take input data from motion capture equipment, such as the VICON system [17] or gaming devices like Nintendo Wii [20] because these devices could provide great details about body motion. The most noticeable work in gestural emotion detection has been done by Camurri and the Infomus Lab [21].…”
Section: B Emotion Detection From Body Languagementioning
confidence: 99%
“…Even though in this study we were yet unable to automatically perform such an analysis, new tools for gesture and affective movements detection are becoming available, and a motion capture system could facilitate the capturing of these different types of behaviors automatically. Berthouze and colleagues (Bianchi-Berthouze and Kleinsmith 2003;Kleinsmith et al 2011;Savva et al 2012) proposed a low-level description of body posture and movement that enable the mapping of bodily expressions into emotion categories or emotion dimensions. By using low-level descriptions of posture, motion capture, and connectionist or statistical modeling techniques to these descriptions, they have suggested that mapping models can easily be adapted to detect different types of expressions irrespective of the context in which these expressions are displayed.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…This method achieved a 61.3 % recognition rate when evaluated at a dataset of recorded body movements of actors who were asked to express freely the six basic emotions. Savva et al [13] proposed an automatic recognition method of affective body movement in the context of a Nintendo Wii tennis game which feeds dynamic movement features to a Recurrent Neural Network (RNN) algorithm. This method was tested at a dataset of nonacted movements captured with Animazoo IGS-190 during gameplay and reached a recognition rate of 57.46 %, comparable with the 61.49 % accuracy of human observers' recognition.…”
Section: Introductionmentioning
confidence: 99%